Efikasi Diri sebagai Mediator Pengaruh antara Dukungan Sosial dan Kecemasan Karier Masa Depan pada Mahasiswa Santri - Permadi, Dimas Agil; Finanin Nur Indana (Jurnal Kajian dan Penelitian Umum, 2026)
Technological developments such as the disruption of artificial intelligence (AI), global economic conditions, and employment uncertainty have triggered high levels of future career anxiety among the younger generation, including university graduates and prospective graduates, including Islamic boarding school students. Ideally, Islamic boarding school students are expected to be more resilient in facing these challenges because pesantren provide them with religious knowledge that teaches acceptance of destiny as well as academic provisions to adapt to the world of work. Responding to this gap, this study aims to examine the role of self-efficacy as a mediator in the relationship between social support and future career anxiety among Islamic boarding school students. This study employed a quantitative correlational design involving 106 Islamic boarding school students in Situbondo. Data were collected using psychological scale instruments, while data analysis was conducted using path analysis through PROCESS Macro Hayes Model 4 with bootstrapping techniques. The results showed that social support had a significant negative effect on future career anxiety (β = -0.612; p < 0.05). Furthermore, self-efficacy was empirically proven to partially mediate this relationship with a significant indirect effect (indirect effect = -0.238; 95% CI [-0.415, -0.102]). Communal support within Islamic boarding schools effectively reduces anxiety because this social protection is internalized into individuals’ confidence in their own capabilities. These findings emphasize the strategic role of Islamic boarding schools not only as emotional safety nets but also as catalysts for strengthening self-efficacy. Strengthening self-efficacy is essential to enable students to transform passive resignation into proactive agency in facing the challenges of the modern labor market.